The politics behind the establishment of United Nations-mandated fact-finding missions: the case of Myanmar - Moore, Gerald Arthur (Department of Political Studies, 2020)
On 9 October 2016, a group of Rohingya militants, equipped with machetes, attacked police stations in northern Rakhine State (nRS), one of the most impoverished states in Myanmar, looting and killing nine police officers and injuring another five. In turn, military and police targeted and attacked Rohingya armed groups, killing many innocent civilians. On 24 March 2017, the European Union, supported by the United States, the United Kingdom and other countries, sponsored a United Nations resolution which gives effect to a UN factfinding mission to determine the facts on violations, especially in Rakhine State. With a view to challenging conventional explanations and views of United Nations-mandated fact-finding, this research study operationalizes a dynamic view of UN fact-finding. At first blush, a strong case can be made that these relatively extensively researched, and verified, across-case dynamics and processes arguably underlie the establishment of the UN-mandated fact-finding mission to Myanmar. However, structural explanations, like the gridlock in the United Nations Security Council (UNSC), do not adequately take into account the timing of the establishment of this United Nations mandated fact-finding mission. The tatmadaw’s military operations have for many years been seen to involve systematic violations of human rights. Crimes such as arbitrary arrest, torture, or forced labour already featured centrally in the work on Myanmar by human rights organizations in the 1980s, and these and many other apparent human rights violations, to a certain extent, continue to preoccupy the United Nations. Furthermore, not only do structural explanations fail to take sufficient account of the dynamic interplay between domestic and international fact-finding and the strategic context in which they are established, but how the UN mission ‗reflects‘ the complexity of Myanmar‘s strategic context, characterised by the emergence and contestation of two audiences of legitimation. In this regard, this research study brings together two branches of scholarly literature‘ and focuses on the politics of the ‗here and now‘ and the contingencies of within case dynamics that underlie the establishment of the UN-mandated fact-finding mission to Myanmar. In this regard, structural explanations cannot fully account for how the UN-mission went from constituting an implicit challenge to the so-called ‗Annan Commission‘ to being framed as ‗complementary‘ to the Annan Commission. Bringing together two bodies of scholarly literature, this research study highlights how four factors in Myanmar‘s strategic context were key to the establishment of the UN-mission, namely, 1. increasing international debate and division over the ‗authority‘ of Aung San Suu Kyi; 2. a political shift within the UN headquarters towards an activist role; and 3. a critique of the United Nations‘ (UN) dominant approach in Myanmar, which has triggered a fourth, namely, 4. the contestation over the identity of the ‗audiences of legitimation.‘ This is most aptly illustrated by the establishment of the UN-mandate fact-finding mission to Myanmar, which ‗reflects‘ the complexity of Myanmar‘s strategic context, characterised by the contestation, navigation and co-optation of these now competing sources of legitimacy: the politics of personality and the politics of Rohingya victimhood. With a view to operationalizing Frederic Megret‘s (2016) ‗dynamic‘ view or conceptualization of international human rights fact-finding, it is argued that the establishment of the UN fact-finding mission to Myanmar is to be understood primarily in the context of the contested nature of the identity of ‗audiences of legitimation‘. Furthermore, this research study employs a process-tracing research methodology, looking to critical historical junctures where explanations challenge conventional wisdom of the literature, for example, that the UN-mandated fact-finding mission is intended to (only) discover the ‗truth about the past‘ or conceptualization of fact-finding that conflate what is ‗factual‘ with ‗the law‘ or presuppose a ‗fact-law distinction‘. Rather, United Nations-mandated fact-finding is a form of ‗discursive practise‘, established (primarily) with a view to the cultivation and maintenance of legitimacy.